Enteric neurones modulate the colonic permeability response to luminal bile acids in rat colon in vivo. (11th February 2004) - Sun, Y; Fihn, B-M; Sjövall, H; Jodal, M
Abstract : Background: The mechanisms behind microscopic colitis and exacerbations of ulcerative colitis are incompletely understood. It seems highly likely that both luminal antigens and bile are involved. The aim of this study was to test the hypothesis that bile acids increase colonic mucosal permeability by activating enteric neurones. Method: The effect of 4 mM deoxycholic acid (DCA) on the appearance rate of intravenously administered 3 H-mannitol and 14 C-urea into the lumen of the proximal and distal rat colon was measured in vivo and expressed as clearance. The nerve blocking agents atropine and hexamethonium were given intravenously, and lidocaine was applied onto the serosal surface of the colon, before and after DCA exposure Results: DCA markedly increased clearance of the permeability probes into the lumen in both colonic segments and also the ratio of mannitol/urea clearance, particularly in the distal colon. Pretreatment with atropine, hexamethonium, and lidocaine significantly inhibited the increase in clearance by approximately 65–80% but did not affect the clearance ratio. In the distal colon, the inhibitory effect of lidocaine was not statistically significant. Also, administration of atropine and hexamethonium after DCA exposure significantly inhibited the DCA effect on clearance of the probes. Conclusion: The results suggest that in vivo, the permeability increase induced by a moderate concentration of bile acid is to a large extent mediated by a neural mechanism involving muscarinic and nicotinic receptors. This mechanism may be a link between the central nervous system and colonic mucosal barrier function, and may be a new target for treatment.